How do network resources affect firms' network-oriented dynamic capabilities? - Alinaghian, Leila; Razmdoost, Kamran (Elsevier, 2017)
While the extant literature investigating the dynamic capabilities that cross the boundaries of firms (i.e., network-oriented dynamic capabilities) has predominantly focused on the identification of their underlying routines or their impact on the firms' performance, the determinants of these routines have largely remained unexplored. Our study seeks to address this issue by investigating how the attributes of network resources (i.e., assets that belong to or are deployed by actors with whom a firm is connected through direct or indirect relationships) influence firms' network-oriented dynamic capabilities. A multiple-case study including 50 network resource sets embedded in 10 business units of five multinational firms spanning pharmaceutical, aircraft power system, and consumer goods' industries is conducted. The findings reveal the effects of eight network resource attributes on the three clusters of network-oriented dynamic capabilities (i.e., sensing, seizing and transforming) as follows: rarity affects the effectiveness of sensing, complementarity affects the effectiveness of seizing, accessibility and usability affect the efficiency of seizing, scalability and appropriability affect the effectiveness of transforming, and finally utility and versatility affect the efficiency of transforming.
Keywords: Network resources; Dynamic capabilities; Interfirm relationships; Network capital; Networking capability; Case study